2022
DOI: 10.21037/mhealth-21-28
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Fitbit devices among children and adolescents with chronic health conditions: a scoping review

Abstract: Background: While Fitbit ® devices were initially intended for leisurely, consumer use, there has been recent interest among scientific and medical communities in the prospective use of Fitbit devices for clinical and research purposes. Those who have chronic health conditions are often required to spend considerable amounts of money and time undergoing physiological tests and activity monitoring to support, stabilize, and manage their health. This disease burden is only amplified in pediatric populations. Dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…A lot of systematic reviews have been published in recent years related to the subject of this review, where the authors [ 73 ] found that the PA level is also influenced by the students’ friends’ PA level, demonstrating that team sports and community life can increase the PA level, promoting the reduction of the obesity-related problems. Another study also verified that using Fitbit devices may benefit increasing the level of PA during recreational activities [ 74 ]. The mobile applications for this subject are more related to the measurements of weight, height, age, gender, goals, and calories needed for calculations, diet diaries and food databases including calories, calories burned and calorie intake [ 75 ].…”
Section: Discussionmentioning
confidence: 83%
“…A lot of systematic reviews have been published in recent years related to the subject of this review, where the authors [ 73 ] found that the PA level is also influenced by the students’ friends’ PA level, demonstrating that team sports and community life can increase the PA level, promoting the reduction of the obesity-related problems. Another study also verified that using Fitbit devices may benefit increasing the level of PA during recreational activities [ 74 ]. The mobile applications for this subject are more related to the measurements of weight, height, age, gender, goals, and calories needed for calculations, diet diaries and food databases including calories, calories burned and calorie intake [ 75 ].…”
Section: Discussionmentioning
confidence: 83%
“…One of the challenges associated with evaluating PA intensity using HR monitors is that HR values are not solely reflective of physical movement and vary secondary to physiologic, emotional, or homeostatic changes. Furthermore, the use of Fitbit models has not been shown to be reliable when measuring HR in individuals with greater levels of disability in SCI54 and children with chronic disorders 42. Additionally, PA monitors cannot differentiate active vs passive movement and therefore cannot ascertain a child’s movement autonomy as compared to caregiver assistance during routine tasks.…”
Section: Discussionmentioning
confidence: 99%
“…"HRpeak" value was the highest HR value in beats per minute (bpm) seen within the 24-hour period of each day of observation. The Fitbit has been shown to be comparable to research-grade models for HR monitoring in typically developing children 41 and feasible for use in children with developmental disorders 42 and individuals who use wheelchairs for primary mobility. 43 Eating and activity journals.…”
Section: Physical Activity Monitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activity trackers such as Fitbit and Garmin devices were initially intended for consumer use, however, there has been increasing interest among scientific and medical communities in their prospective use for clinical and research purposes. 10,11 The purpose of this study was to explore the most effective, practical and acceptable way to measure PA in young people with haemophilia and to compare agreement in daily step count and time spent in mod- Participants were provided with a Fitbit Charge 3 and a Garmin Vivosport device for 2 weeks each (in random order) and an ActiGraph GT9X-BT for the same 4-week period and asked to wear the devices as much as possible during waking hours. In line with the protocol by…”
Section: Dear Editormentioning
confidence: 99%